Analysing the determinants of performance of best and worst European banks: A mixed logit approach - Barros, Carlos Pestana; Ferreira, Candida; Williams, Jonathan (Journal of Banking & Finance, 2007)
Using a dataset of 7635 observations on 1384 commercial banks operating in the EU between 1993 and 2001, we utilise a mixed logit model to identify factors that explain the probability of a bank being a best [worst] performer. The empirical evidence confirms the importance of country-level characteristics (location and legal tradition), and firm-level features (bank ownership, balance sheet structure and size). Specifically, smaller sized banks with higher loan-intensity, and foreign banks from countries upholding common law traditions have a higher probability of best performance.